Negative association between dietary copper intake and human papillomavirus infection: A cross-sectional analysis of the National Health and Nutrition Examination Survey - Chengya Feng; Xiaohe Lu; Zimian Fan; Xinxing Wang (PLoS ONE, 2025)
Background Human papillomavirus (HPV) is the most prevalent sexually transmitted infection. Copper is essential for immune function, but its association with HPV infection remains unclear. This study aims to investigate the relationship between dietary copper intake and HPV infection. Methods This cross-sectional study analyzed 8,071 participants from the National Health and Nutrition Examination Survey (2003–2016). Copper intake was assessed using two 24-hour recalls, and HPV status was confirmed by DNA testing. Weighted multivariable logistic regression and restricted cubic splines (RCS) were used. Results After adjusting for multiple confounders, dietary copper intake was significantly inversely associated with vaginal HPV infection (odds ratio [OR], 0.79; 95% confidence interval [CI], 0.67–0.92). Compared with women in the lowest quartile of dietary copper intake, those in the highest quartile had a lower adjusted OR for vaginal HPV infection (OR, 0.60; 95% CI, 0.48–0.73). RCS analysis revealed an L-shaped association with a threshold at 1.2 mg/day of copper intake. Subgroup analyses showed that marital status moderated the association between copper intake and HPV infection (P for interaction < 0.001), with significance in those married or living with a partner but not in those living alone. Conclusion An L-shaped association was observed between copper intake and HPV infection, suggesting that maintaining an optimal level of copper intake may be associated with reduced risk of HPV infection and related diseases.